Heart failure hospitalization in adult patients with congenital heart disease: risk factors for repeated admissions. (14th October 2021) - Scherrenberg, H; De Meester, P; Troost, E; Santens, B; Moons, P; Budts, W; Van De Bruaene, A
Abstract: Background: Heart failure hospitalizations in adult patients with congenital heart disease (ACHD) are increasing and are associated with higher healthcare-related costs. We aimed to evaluate factors that are associated with repeated heart failure hospitalizations and whether heart failure hospitalizations are related to adverse outcome in ACHD patients with heart failure (ACHD-HF). Methods: Out of 3995 patients under active follow-up in our institution (last visit >2010), 256 patients (mean age 49.5±16.7 years) had ACHD-HF and were included in the study. Medical records were reviewed, including heart failure hospitalization prior and after study inclusion. A combined endpoint of death, ventricular assist device and transplantation was defined. Results: Overall, 136 ACHD-HF patients (53%) had a prior heart failure hospitalization. Over a mean follow-up of 2.5±2.3 years, 44 patients (17%) had repeated heart failure hospitalizations. Of these, 31 patients (12%) had 1; 9 patients (4%) 2 and 4 patients (2%) 3 repeated heart failure hospitalizations. Patients with repeated heart failure hospitalizations had higher NYHA class (p=0.031), were more likely to have end-organ dysfunction (p=0.025) and more likely to have a prior heart failure hospitalization (p<0.001). In multivariable Cox regression analysis, only end-organ dysfunction (HR 2.431 95% CI 1.516–43.896 p<0.001) was related to repeated hospitalization. Seventy patients (27%) reached the combined endpoint of death, VAD or transplantation (event-rate 11% per year). Repeated heart failure hospitalizations was not related to the combined endpoint in Cox regression analysis. Conclusions: Heart failure hospitalizations are frequent in ACHD-HF. End-organ dysfunction appears to be a strong determinant of repeated heart failure hospitalizations. Event-rate is high in patients with ACHD-HF, but repeated heart failure hospitalizations were not related to outcome in this short-term follow-up study. FUNDunding Acknowledgement: Type of funding sources: None.